Peran Ukuran Bank dalam Memoderasi Kinerja Keuangan Terhadap Tingkat Bagi Hasil Deposito Mudharabah pada Bank Syariah di Indonesia Tahun 2019-2023 - Muhammad Kevin Alfianto; Dimas Emha Amir Fikri Anas; Ati Retna Sari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study provides an analysis of the role of financial performance in the profit-sharing rate of mudharabah deposits at Islamic Commercial Banks in Indonesia by measuring financial performance through Operating Expenses to Operating Income (BOPO), Non-Performing Financing (NPF), and Return on Assets (ROA). Additionally, the study evaluates the role of Bank Size as a moderating variable in these relationships. Using a quantitative approach, the study involved 8 Islamic Commercial Banks as samples during the 2019–2023 period. Data analysis was conducted using the Moderated Regression Analysis method to examine the direct effects of independent variables and the moderating effect of Bank Size. The findings reveal that BOPO does not have a significant impact on the profit-sharing rate of mudharabah deposits. However, NPF and ROA were found to significantly affect the profit-sharing rate. Furthermore, Bank Size was proven unable to moderate the relationship between BOPO, NPF, and ROA with the profit-sharing rate of mudharabah deposits.